Komunitas Digital AIMI dan Gerakan Sosial Berbasis Facebook - Kusumaningrum, Demeiati Nur; Hardyanti, Winda; Pradana, Hafid Adim (Universitas Muhammadiyah Yogyakarta, 2017)
This study describes the Association of Breastfeeding Mothers Indonesia (AIMI) as an NGO that has built social movements to support breast feeding and nursing mothers in Indonesia. AIMI as a socio-political actor shapes the perception and behaviour of society to ensure the maternity right that has been recognized by the World Health Organization (WHO). This research uses qualitative-descriptive method with inductive approach. The data obtained through the online media content analysis, interviews, and literature study. It concludes thatfacebook became instrument of internalization of ideas, the dissemination of ideas, and claims of truth for AIMI where: 1) Breast milk is the best food for infants, 2) nursing is a baby and mother’s rights that should be supported through government policy and infrastructure, and 3) breastfeeding barriers experienced by mothers can be overcome with well established methods and knowledge. AIMI’s digital community was createdinteraction in the form of presents text and images that lead to perceptions and behaviour indirectly strengthen the enactment of Government Regulation No. 33 in 2012 and 2013 Permenkes No. 15. The online publicationhas involved AIMI campaigns, educational information, socialization, training and consulting through facebook or discussion service with Lactation Counselor.Penelitian ini menggambarkan Asosiasi Ibu Menyusui Indonesia (AIMI) sebagai LSM yang membangun gerakan sosial untuk mendukung pemberian ASI dan hak ibu menyusui di Indonesia.AIMI sebagai aktor sosial-politik membentuk persepsi dan perilaku masyarakat untuk menjamin hak maternitas yang telah diakui oleh Organisasi Kesahatan Dunia (WHO). Penelitian ini menggunakan metode kualitatif-deskriptif dengan pendekatan induktif. Datadiperoleh melalui analisis konten media daring, wawancara, dan studi literatur.Hasil penelitian menyimpulkan facebookmenjadiinstrumen internalisasi ide, penyebaran gagasan, dan klaim kebenaran AIMIdi mana: 1) ASI merupakan makanan terbaik bagi bayi, 2) menyusui merupakan hak bayi dan ibu yang harus didukung melalui kebijakan dan infrastruktur, dan 3) kendala menyusui dapat diatasi dengan metode yang tepat dan pengetahuan yang mapan.Komunitas digital AIMI menghadirkan interaksi dalam bentuk teks dan gambar yang mengarah pada persepsi dan perilaku yang secara tidak langsung menguatkan pemberlakuan Peraturan Pemerintah No 33 Tahun 2012 dan Permenkes No 15 Tahun 2013. AIMI melakukan publikasi daring meliputi kampanye,informasi edukatif, sosialisasi pelatihan, dan konsultasi melalui diskusi facebook atau layanan Konselor Laktasi.